2019
DOI: 10.1089/ars.2017.7411
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Glutaredoxin in Brain Cells—Implications for Parkinson's Disease

Abstract: Further investigation is needed to understand the preponderant role of Grx1 regarding dopaminergic neuronal survival. Antioxid. Redox Signal. 00, 000-000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 134 publications
(163 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, analyses of qRT-PCR, Western blotting, ELISA, CCK-8 assay and flow cytometry elaborated that miR-132-3p interfered with microglial activation and neuronal injury by targeting GLRX. Our data are in agreement with the earlier findings showing that enhancement of GLRX activity in these brain cells would impede the progression of PD ( Gorelenkova Miller and Mieyal, 2019 ). MPTP is a neurotoxin that results in a profound reduction of striatal dopamine levels and specific loss of dopaminergic neurons in animals ( Lee et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, analyses of qRT-PCR, Western blotting, ELISA, CCK-8 assay and flow cytometry elaborated that miR-132-3p interfered with microglial activation and neuronal injury by targeting GLRX. Our data are in agreement with the earlier findings showing that enhancement of GLRX activity in these brain cells would impede the progression of PD ( Gorelenkova Miller and Mieyal, 2019 ). MPTP is a neurotoxin that results in a profound reduction of striatal dopamine levels and specific loss of dopaminergic neurons in animals ( Lee et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
“…Grx is an essential thioltransferase whose primary role is to reduces S-glutathionylation. Grx 1 insufficiency results in increased levels of S-glutathionylation, implicated in many pathological events, including cardiovascular [56] and Parkinson's [57] diseases. Since Grx catalyzes GSH-dependent reduction of S-glutathionylation, lower GSH:GSSG ratio might attenuate Grx activity, mimicking Grx deficiency.…”
Section: The Biological Meaning Of Protein S-glutathionylationmentioning
confidence: 99%
“…Since Grx catalyzes GSH-dependent reduction of S-glutathionylation, lower GSH:GSSG ratio might attenuate Grx activity, mimicking Grx deficiency. In contrast, Grx 1 plays a primary proinflammatory role in microglia [57] or an anti-angiogenic role in the vasculature [58]. More than one hundred S-glutathionylation proteins have been experimentally verified.…”
Section: The Biological Meaning Of Protein S-glutathionylationmentioning
confidence: 99%
“…Recent studies showed that overexpression of Grx1 inhibited monocyte chemotaxis induced by MCP-1 (48), and Grx1 KO mice are more susceptible to pulmonary fibrosis (49). Elevated Grx1 activity diminishes the development of Parkinson's disease (50). However, few studies have reported interactions of Grx1 and VLA4 in those processes, which need further investigation.…”
Section: Regulation Of ␣4 Integrin By Glutathionylationmentioning
confidence: 99%